The Interlanguage Interference on the Difficulties of Building Question Sentences by the Second Year Students of MA As Soorkaty Salatiga - Sari Famularsih (UIN Salatiga, 2014)
This study is aimed to elaborate the interlanguage interference of the difficulties which are faced by 40 second year students of MA As Soorkaty Salatiga in academic year of 2004-2005 in building question sentences and the sources of difficulties. The research is conducted by such kind of test. The total number of test are 20 items, consist of 5 yes-no questions, 5 W-H questions, and 10 tag questions which is done in a written essay form. Based on the analysis, the result shows some conclusions. Firstly, the researcher finds the types of difficulties problems are faced by the students in building question mastery, such as: (1) building yes-no question sentences in translation the word “apakah”, that is related with the use of to be. (2) Building interrogative word question sentences in translation the words “apa”, “kapan”, “milik siapa”, etc. That are related with the use of “what”, “when”, “whose”, etc. (3) Completing the tag question sentences with the proper auxiliary based on tense of the sentences. The most difficulties in building question sentences are especially in yes-no question form by using the word “apakah”. In the term of interlanguage, the students’ errors are mostly included in expressing meaning by the words and grammar of the first language. The source of difficulties which have been analyzed are mostly caused by inter lingual and intra lingual transfer. Keywords: Interlanguage; Question Sentence; Interlingual Transfer; Intralingual Transfer